2018
DOI: 10.1021/acssuschemeng.8b01885
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Highly Monodispersed, Stable, and Spherical NZVI of 20–30 nm on Filter Paper for the Removal of Phosphate from Wastewater: Batch and Column Study

Abstract: A nanobiodegradable adsorbent was prepared by stabilizing nanoscale zerovalent iron (NZVI) on cellulose filter paper. Characterization of the sample disclosed that the NZVI particles were rounded, well-monodispersed through the paper, and smaller than 30 nm in diameter. We explored this material's ability to capture phosphate ions in batch and repeated operations, specifically studying the impact of pH, adsorption time, initial phosphate concentration, interference ions, and temperature. The equilibrium result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…Spectra were recorded in the range of 4000-400 cm −1 using KBr pellets. 45 Differential scanning calorimetry. Samples were heated from 30°C to 275°C under 70 ml min −1 inert N 2 gas at a heating rate of 10°C min −1 using a Netzch 204 F1 Phoenix DSC equipped with an intra-cooler system.…”
Section: Chemical and Analytical Characterization 1 H-nuclear Magnetimentioning
confidence: 99%
“…Spectra were recorded in the range of 4000-400 cm −1 using KBr pellets. 45 Differential scanning calorimetry. Samples were heated from 30°C to 275°C under 70 ml min −1 inert N 2 gas at a heating rate of 10°C min −1 using a Netzch 204 F1 Phoenix DSC equipped with an intra-cooler system.…”
Section: Chemical and Analytical Characterization 1 H-nuclear Magnetimentioning
confidence: 99%
“…To obtain scanning electron microscopy (SEM) images, HIPEs were placed onto a silicon wafer, freezedried, and sputtered with gold. 21 The porous structures of the HIPEs were observed on a LEO 1550 SEM equipped with a GEMINI field emission column. The morphology of the fresh HIPEs was characterized by cryo-SEM.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Nanoscale zero valent iron (NZVI) as a nano-adsorbent is used for water remediation, but its easy aggregation leads limits it reactivity and stability. 89 Benefiting from the biocompatibility and porosity of cellulose paper, Arshadi et al 90 reported the preparation of NZVI monodispersed filter paper for the sequestration of phosphate ions from wastewater. The resulting paper displayed a remarkable phosphate removal efficiency of 99.9% for certain phosphate ion amounts and contact times and exhibited high reusability after 7 adsorption–desorption cycles.…”
Section: Cellulose-based Papermentioning
confidence: 99%